Stock market liberalization impact on sectoral stock market return in Malaysia - Maniam, Subashini; Chin, Lee (Malaysian Finance Association, 2018)
The stock market liberalization policies announcement dates shows that the liberalization policies were implemented on specific sectors in Malaysia instead of the whole stock market in the country. Therefore, this paper analyses the impact of stock market liberalization on sectoral stock market return in Malaysia, in particular finance sector and service sector. Dynamic Fixed Effect (DFE) method was used to study the stock market liberalization impact on the stock market return while controlling the effects of stock market characteristics, which are stock market size, volatility and liquidity. The results indicate that, in the long run stock market liberalization has positive effect on stock market return only for the service sector, but no significant impact on finance sector’s stock return.